XML basics - Banzal, S. (Mercury Learning and Information, 2020)
Focusing on standards that are relevant to almost all developers working with XML, this book investigates XML technologies that span a wide range of XML applications and provides numerous code samples that show exactly how XML is used in myriad applications. -- Edited summary from book.
Includes index.
Keywords: Programming languages.; XML.; elektronické knihy; electronic books